2014
DOI: 10.4196/kjpp.2015.19.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory, Antioxidant and Antimicrobial Effects of Artemisinin Extracts fromArtemisia annuaL.

Abstract: The anti-inflammatory, antioxidant, and antimicrobial properties of artemisinin derived from water, methanol, ethanol, or acetone extracts of Artemisia annua L. were evaluated. All 4 artemisinin-containing extracts had anti-inflammatory effects. Of these, the acetone extract had the greatest inhibitory effect on lipopolysaccharide-induced nitric oxide (NO), prostaglandin E2 (PGE2), and proinflammatory cytokine (IL-1β , IL-6, and IL-10) production. Antioxidant activity evaluations revealed that the ethanol extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(84 citation statements)
references
References 39 publications
1
83
0
Order By: Relevance
“…The main ingredients of the essential oil of A. annua are beta‐pinene, alpha‐pinene, camphor, camphene, 1,8‐cineole, artemisia ketone, myrcene, borneol, linalool, and beta‐caryophyllene . The pharmacological effects of A. annua include its antimalarial, antioxidant, anti‐inflammatory, antimicrobial, immunomodulatory, and anticancer properties. A variety of compounds have been isolated from A. annua such as coumarins, flavonoids, sesquiterpenoids, triterpenoids, phenolics, and artemisinin…”
Section: Resultsmentioning
confidence: 99%
“…The main ingredients of the essential oil of A. annua are beta‐pinene, alpha‐pinene, camphor, camphene, 1,8‐cineole, artemisia ketone, myrcene, borneol, linalool, and beta‐caryophyllene . The pharmacological effects of A. annua include its antimalarial, antioxidant, anti‐inflammatory, antimicrobial, immunomodulatory, and anticancer properties. A variety of compounds have been isolated from A. annua such as coumarins, flavonoids, sesquiterpenoids, triterpenoids, phenolics, and artemisinin…”
Section: Resultsmentioning
confidence: 99%
“…; Kim et al . , ). Furthermore, flavonoids isolated from A. annua leaves are known active anti‐malarial and anti‐cancer agents, through the action of artemisinin (Weathers et al .…”
Section: Introductionmentioning
confidence: 99%
“…polymorphum , and Prevotella intermedia . Polyphenol‐containing extracts exhibit antimicrobial activities on Actinobacillus actinomycetemcomitans (Kim et al, ). The result confirms a previous study that reported that artemisinin‐containing water solution extracts had antimicrobial activity against A. actinomycetemcomitans .…”
Section: Pharmacological Properties Of Artemisininmentioning
confidence: 99%
“…Therefore, the artemisinin and hemin combination might have a synergetic antiviral activity. (Kim et al, 2015).…”
Section: Antiviral Effectmentioning
confidence: 99%